(untitled) (Bangladesh Journal of Medicine, 2016)
DandyWalker malformation (DWM) is a uncommon intracranial congenital abnormality that affects the cerebellum and some of its components; particularly cerebellar vermis, fourth ventricle and is characterized by an enlarged posterior fossa. Although there is an extensive list of signs attributed to DWM, final diagnosis is solely dependent on imaging techniques as there are no signs that are characteristic of DWM. This article reports a case with DWM who was diagnosed by magnetic resonance imaging. Bangladesh J Medicine Jan 2016; 27(1) : 33-36